2021
DOI: 10.1016/j.ceramint.2020.08.202
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose derived microporous–mesoporous carbon for advanced lithium–sulfur batteries

Abstract: Sucrose derived microporous-mesoporous carbon for advanced lithium-sulfur batteries. Ceramics International, 47 (1). pp. 899-906.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 65 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Large mesopores and macropores can provide good ion transport channels and electrolyte infiltration channels. 26 To sum up, BHPC-4 with three-stage nested pore structure is speculated the best electrochemical feature, due to positive fast kinetics of carbon-based sulfur trestle. Then BHPC-4 and BHPC-4/S composite were further characterized.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Large mesopores and macropores can provide good ion transport channels and electrolyte infiltration channels. 26 To sum up, BHPC-4 with three-stage nested pore structure is speculated the best electrochemical feature, due to positive fast kinetics of carbon-based sulfur trestle. Then BHPC-4 and BHPC-4/S composite were further characterized.…”
Section: Resultsmentioning
confidence: 97%
“…Micropores and small mesopores can restrict the dissolution and the “Shuttling Effect” of polysulfide during cycling. Large mesopores and macropores can provide good ion transport channels and electrolyte infiltration channels 26 . To sum up, BHPC‐4 with three‐stage nested pore structure is speculated the best electrochemical feature, due to positive fast kinetics of carbon‐based sulfur trestle.…”
Section: Resultsmentioning
confidence: 99%
“…1 B , Inset ). Using as the sulfur host, the synergy of macro-/meso-/microporous triple structure not only can ensure high sulfur utilization and anchor sulfur/sulfides firmly but also can provide good ion transport channels and effectively relieve the volume expansion of sulfur particles upon cycling, which facilitates to realize the fast kinetics and long-life cycling stability of sulfur-based batteries ( 33 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] These problems inevitably lead to low sulfur utilization rate, severe structural instability, limited capacity, rapid capacity decay, poor coulomb efficiency and so on. [4][5][6][7][8] To handle these challenges, various carbon/sulfur composites, such as nanostructured porous conducting carbon (e.g., Micro/mesoporous carbon, carbon nanotubes (CNTS), graphene, activated carbon), [9][10][11][12][13] have been paid close attention by improving electrode conductivity, providing fast ion/electron transport paths and capturing polysulde via physical domain. For instance, Nazar et al 9 reported a simple and widely available method for encapsulating sulfur into the porous structure of ordered mesoporous carbon (CMK-3) to provide both electrical contacts with sulfur and adequate controlled porosity for trapping polysuldes species.…”
Section: Introductionmentioning
confidence: 99%